The Vital Role of Faith Communities in the Lives of Urban Refugees - Michael D Crane (International Journal of Interreligious and Intercultural Studies, 2020)
The majority of the worldâ€™s refugees do not live in refugee camps, but in cities around the world. Realities for urban refugees are vastly different from the conditions of a refugee camp. Urban refugees lack the institutional supports of official refugee camps and often have minimal legal covering in their host cities. Without government support and the limited capacity of UNHCR to provide adequate help, it is left to citizens of the host cities to provide help. Kuala Lumpur (KL) is home to more than 150,000 refugees and even more asylum seekers. These population numbers could be overwhelming to a city without help from its citizenry. This paper will examine ways in which Christian churches have welcomed and helped this large refugee population when few others would help. Guided by a biblical command to welcome â€œthe strangerâ€, churches have sacrificed greatly to impact the lives of refugees in several key areas: education, employment, health care, and spiritual vitality. Because faith communities operate outside of governmental and non-governmental bureaucratic structures, their work often goes unnoticed. The work of these faith communities in KL is not an isolated event but serves as one case study of similar work happening in cities all over the world.